2022
DOI: 10.1108/er-10-2021-0441
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ fit to telework and work well-being: (in)voluntariness in telework as a mediating variable?

Abstract: PurposeThe present study aims to examine the mediating role of (in)voluntariness in teleworking in explaining the relationship between employees’ fit to telework and work well-being (i.e. work engagement and exhaustion).Design/methodology/approachA cross-sectional survey design was used in this study. The sample comprised 222 individuals performing telework in Portugal. Statistical analyses employed were descriptive statistics, Pearson’s correlation, confirmatory factor and structural equation analyses, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 64 publications
(162 reference statements)
0
10
0
Order By: Relevance
“…However, employees with high remote work preferences experienced remote work to affect well-being directly and positively (Erro-Garcés et al , 2022). Perceptions may also depend on employee age, gender (Kirchner et al , 2022), and whether remote work is enforced or voluntary (Kirchner et al , 2022; Kaluza and van Dick, 2022; Lopes et al , 2022), and on industry, occupation, job and personal characteristics of the remote worker (Beckel and Fisher, 2022; Nenonen and Sankari, 2022). In addition, the location of remote work (Morganson et al , 2009), the design and condition of the home office (Ng, 2010), the quality of job crafting (Stempel and Siestrup, 2022), the amount of remote work (Niebuhr et al , 2022) and national conditions (Ipsen et al , 2022) may affect well-being and performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, employees with high remote work preferences experienced remote work to affect well-being directly and positively (Erro-Garcés et al , 2022). Perceptions may also depend on employee age, gender (Kirchner et al , 2022), and whether remote work is enforced or voluntary (Kirchner et al , 2022; Kaluza and van Dick, 2022; Lopes et al , 2022), and on industry, occupation, job and personal characteristics of the remote worker (Beckel and Fisher, 2022; Nenonen and Sankari, 2022). In addition, the location of remote work (Morganson et al , 2009), the design and condition of the home office (Ng, 2010), the quality of job crafting (Stempel and Siestrup, 2022), the amount of remote work (Niebuhr et al , 2022) and national conditions (Ipsen et al , 2022) may affect well-being and performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Remote work requires employees to be relatively self-sufficient and autonomous (Lopes et al, 2023;Malinen, Wong, & Naswall, 2020). In research on blended working arrangements pre-COVID-19, Wörtler, Van Yperen, and Barelds (2021) found that autonomy orientation led to positive attitudes toward the organization.…”
Section: Individual Factorsmentioning
confidence: 99%
“…The salience of autonomy was evident in the comments of some of our participants, who either appreciated or criticized the degree of autonomy they were given in lockdown. Those who valued autonomy experienced an improved fit either between their actual work and work preferences (person-job fit) or between their actual autonomy and need for autonomy (needs-supplies fit) (Lopes et al, 2023). Some participants suggested that their introverted personalities contributed to psychological comfort while WFH, while the extroverted missed the social contact in the office.…”
Section: Individual Factorsmentioning
confidence: 99%
See 2 more Smart Citations